Pengembangan TPA Sabilil Falaq melalui Penguatan SDM Pengajar di Gampong Janguet, Indra Jaya, Aceh Jaya - Analiansyah; Tiara Nur Mulyawati; M. Fauzi; Ahmad Roy Suli; Salwa Athifah; M. Zikrillah; Ansarullah Ansarullah; Jemadin Jemadin; Rezka Pebrina Kusuma Putri; Muhammad Mirdasil Aslami (Jurnal Riset dan Pengabdian Masyarakat, 2023)
The quality of human resources is actually determined by the level of education. Quality and character education will certainly produce quality and character human beings. Al-Qur'an Education Park (TPA) is a place for non-formal education to study religious knowledge among children. The existence of the Qur'an education park is used as an effort to increase the knowledge of Islamic religious knowledge and character in children. Al-Quran education park has a major role to teach the ability to read and write the Koran. On this occasion, Serumpun Malay KKN students provided assistance and development at the Sabilil Falaq TPA related to strengthening the teaching staff of the Sabilil Falaq TPA. The method used is a qualitative method with data collection techniques, namely interview surveys, documentation, and field research. The results obtained are that there are several problems at TPA Sabilil Falaq, namely, the number of students is more than the number of teachers, the ability of teachers is still standard, and the lack of learning media in learning. The solution provided is to make efforts to add teaching teachers or to cadre students who are already capable, carry out training for Koran teachers, and provide fun and innovative learning media.